Alejandro Gaviria, I don't expect to make that trip (On Stefan Zweig's connections to Colombia and the madness of war). Bogota: Ariel. Editorial Planeta SA 2022,179 pages. - López-González, Rosendo; Ramírez-Valencia, Astrid (Visión electrónica, 2023)
Alejandro Gaviria, I don't expect to make that trip